2015
DOI: 10.1371/journal.pone.0143997
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infection and Wild Animal Health: Effects of Trypanosomatids and Gastrointestinal Parasites on Coatis of the Brazilian Pantanal

Abstract: Wild animals are infected by diverse parasites, but how they influence host health is poorly understood. We examined the relationship of trypanosomatids and gastrointestinal parasites with health of wild brown-nosed coatis (Nasua nasua) from the Brazilian Pantanal. We used coati body condition and hematological parameters as response variables in linear models that were compared using an information theoretic approach. Predictors were high/low parasitemias by Trypanosoma cruzi and T. evansi, and indices repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 87 publications
4
20
0
2
Order By: Relevance
“…Indeed, model analysis for abundance of acanthocephalan eggs in coatis indicated that host sex was an important predictor of infection; male coatis seem to be more affected by parasitism, especially during the breeding season, which may in turn favor higher parasite intensities. Olifiers et al (2015) found similar results for Trypanosoma evansi infection in coatis from the same study site.…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, model analysis for abundance of acanthocephalan eggs in coatis indicated that host sex was an important predictor of infection; male coatis seem to be more affected by parasitism, especially during the breeding season, which may in turn favor higher parasite intensities. Olifiers et al (2015) found similar results for Trypanosoma evansi infection in coatis from the same study site.…”
Section: Discussionsupporting
confidence: 75%
“…Finally, Olifiers et al (2015) reported that body condition was lower in wild coatis (Nasua nasua) with high parasitemia of T. evansi than those which tested negative, especially during the reproductive season. This is in agreement with our observations, but it should be taken into account that our cross-sectional results cannot distinguish cause from effect (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…There is experimental evidence in mice, rats, dogs, donkeys, horses and coatis that T. evansi cause anemia following the first wave of parasitemia (Aquino et al 2002;Herrera et al 2002). In dogs, horses and freeliving animals such as coati, lower red blood cell counts (RBC) were reported in animals with high parasitemia (Herrera et al 2004;Olifiers et al 2015). Similarly, capybaras infected with T. evansi showed lower mean RBC counts than those not infected animals, however this difference was not significant (p = 0.063).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations